2021
DOI: 10.3390/pharmacy9020098
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Survey among General Population Regarding Knowledge and Attitude toward Antibiotic Usage in Western Saudi Arabia

Abstract: Background: Antibiotic resistance is a threatening issue to human wellbeing and an obstacle in the treatment process of many life-threating illnesses. This study aims to assess the knowledge and attitudes toward antibiotic usage among the general population in Jeddah, Saudi Arabia. Methods: A self-administered cross-sectional survey of 460 participants was distributed among the general population in Jeddah in the form of a validated questionnaire. Sample size was calculated to be 460 adults of either gender. D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 25 publications
4
11
0
Order By: Relevance
“…They proved to have less accurate knowledge and responded in the highest percentage (69.19%, n = 1332). Similarly, the youngest age group responded in a larger proportion compared to other recent studies on the same subject [ 70 ]. In terms of attitudes toward antibiotic consumption, this study reveals that 52.73% of respondents try to have an antibiotic in the house, which can be determined by the concern and insecurity related to the COVID-19 crisis.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…They proved to have less accurate knowledge and responded in the highest percentage (69.19%, n = 1332). Similarly, the youngest age group responded in a larger proportion compared to other recent studies on the same subject [ 70 ]. In terms of attitudes toward antibiotic consumption, this study reveals that 52.73% of respondents try to have an antibiotic in the house, which can be determined by the concern and insecurity related to the COVID-19 crisis.…”
Section: Discussionsupporting
confidence: 55%
“…Various other studies have shown that other populations are less disciplined when it comes to completing antibiotic treatment. For example, 42.1% of Hong Kong respondents [ 73 ], 55.1% of the respondents from Western Saudi Arabia [ 70 ] or 51.5% of the Lebanese population [ 58 ] stopped their course of antibiotics if their symptoms improved. The best example was reported by Sweden [ 64 ], where less than 5% of the population would discontinue the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…More than half (64%) had the misconception that antibiotics are effective against viral infections; 32% believed that they should stop their prescribed course of antibiotics when they feel better, and 76% mistakenly thought that AMR is due to the human body, instead of bacteria, becoming resistant to antibiotics [ 6 ]. Several other studies reported similar observations due to poor antibiotic and AMR knowledge among the general public [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ]. Population-based educational campaigns, however, have been found to have either mixed or no effect on improving knowledge and appropriate antibiotic practices, suggesting a need for more targeted approaches in tailoring education for specific sub-populations [ 16 , 17 ].…”
Section: Introductionsupporting
confidence: 57%
“…Recent research at the time of writing this paper was published in 2021 and studied the population of Jeddah city. Their work confirms our findings of poor KAP towards antibiotics and antimicrobial resistance in society [14].…”
Section: Discussionsupporting
confidence: 90%
“…It also suggests reducing antibiotic misuse by raising awareness [ 13 ]. Low knowledge levels were also reported in a 2021 study in Jeddah, indicating the need to increase public knowledge and raise awareness [ 14 ]. Globally, in Kuwait, a KAP study on antibiotic use in 2015 [ 15 ] reported that 72.8% of the respondents had received an antibiotic prescription in the year before the survey; of those, 36% did not complete the course of treatment.…”
Section: Introductionmentioning
confidence: 99%